Discovery and biological characterization of potent myeloid cell leukemia‐1 inhibitors. Issue 1 (19th December 2016) - Lee, Taekyu; Bian, Zhiguo; Zhao, Bin; Hogdal, Leah J.; Sensintaffar, John L.; Goodwin, Craig M.; Belmar, Johannes; Shaw, Subrata; Tarr, James C.; Veerasamy, Nagarathanam; Matulis, Shannon M.; Koss, Brian; et al.
Abstract : Myeloid cell leukemia 1 (Mcl‐1) is an antiapoptotic member of the Bcl‐2 family of proteins that when overexpressed is associated with high tumor grade, poor survival, and resistance to chemotherapy. Mcl‐1 is amplified in many human cancers, and knockdown of Mcl‐1 using RNAi can lead to apoptosis. Thus, Mcl‐1 is a promising cancer target. Here, we describe the discovery of picomolar Mcl‐1 inhibitors that cause caspase activation, mitochondrial depolarization, and selective growth inhibition. These compounds represent valuable tools to study the role of Mcl‐1 in cancer and serve as useful starting points for the discovery of clinically useful Mcl‐1 inhibitors. PDB ID codes: Comp.2 :5IEZ ; Comp.5 :5IF4 . Abstract :